mTORC1 Is Not Principally Involved in the Induction of Human Endotoxin Tolerance - Ludwig, Kristin; Husain, Ralf A.; Rubio, Ignacio (Frontiers in Immunology, 2020)
Endotoxin tolerance represents a safeguard mechanism for preventing detrimental prolonged inflammation and exaggerated immune/inflammatory responses from innate immune cells to recurrent harmless pathogens. On the other hand, excessive immune tolerance can contribute to pathological immunosuppression, as present e.g. in sepsis. Monocyte activation is accompanied by intracellular metabolic rearrangements that are reportedly orchestrated by the metabolic signalling node mTORC1. mTORC1-dependent metabolic re-wiring plays a major role in monocyte/macrophage polarization, but whether mTORC1 participates in the induction of endotoxin tolerance and other immune adaptive programms such as immune training is not clear. This connection has been difficult to test in the past due to the lack of appropriate models of human endotoxin tolerance allowing for genetic manipulation of mTORC1. We have addressed this shortcoming by investigating monocytes from Tuberous Sclerosis (TSC) patients that feature a functional loss of the tumor suppressor TSC1/2 and a concomitant hyperactivation of mTORC1. Subjecting these cells to various protocols of immune priming and adaptation showed that TSC monocytes are not compromised in the induction of tolerance. Analogously, we find that pharmacological mTORC1 inhibition does not prevent endotoxin tolerance induction in human monocytes. Interestingly, neither manipulation affected the capacity of activated monocytes to switch to increased lactic fermentation. In sum, our findings document that mTORC1 is unlikely to be involved in the induction of endotoxin tolerance in human monocytes and argue against a causal link between an mTORC1-dependent metabolic switch and the induction of immune tolerance.